A novel method to monitor lower limb muscles flexibility in young elite athletes: Is it examiner-dependent? - Materne, O.; Fourchet, F.; Hudacek, T.; Buchheit, M. (7th World Congress on Science and Football (WCSF), 2011, 2011)
Lack of flexibility and muscles length imbalances can increase injury risk in soccer1. Most flexibility tests are subjectively defined by subject`s tolerance. We have developed a new method using standardized stretch force2. While the reliability of this method has been described (day-to-day CV 2.6-12.4%), whether switching staff can affect the results is unknown. The aim of the present study was to examine whether the reliability of the measures obtained through this method is examiner-dependent. Methods Ten young male athletes (age: 15.3±1.6 yrs, body mass: 65.4±26.2 kg, height: 171.7±8.8 cm and 1.5±1.5 years from peak height velocity) training in a sport academy were evaluated on two occasions (3 days apart). The flexibility of 8 lower limb muscle groups was examined on both sides in two phases: a video capture of the measured angle by three distinct pairs of operators, and a computer-aided analysis of the video clips by three distinct analyzers. The reliability of the measures was assessed by calculating the typical error of measurement, expressed as a coefficient of variation (CV, 90% CI). Then, between-analyzers and between-operators differences in average CV were expressed as Cohen`s d (90% confidence interval, 90% CI). No substantial difference was considered if Cohen`s d < 0.2 and the 90% CI included zero. Results & Discussion As illustrated in figure 1, there was no substantial difference in CV, either between operators or analyzers. There was no substantial difference between all possible analyzers/operators combinations. To our knowledge, this is the first time that the potential effect of various operator/analyzer combinations on the reliability of flexibility measures has been reported with such a method. Conclusion The reliability of the method to monitor flexibility was examiner-independent, which provides the option to switch staff without affecting the results. These findings reinforce the practical use of this method in soccer teams/academies and may be of interest in pre-season screening to identify players at risk of injury due to flexibility imbalances or deficits.